(untitled) (Clinics, 2007)
OBJECTIVE: The aim of this study was to analyze the effect of glucosamine sulfate on the tibial epiphyseal disk of the ovariectomized rats. METHODS: After ovariectomy (OVx), 28 female rats were randomly divided into 4 experimental groups with 7 animals each, treated as follows: OVx 21 - vehicle (NaCl 0.9%) 0.5 mL/day) for 21 days; OVx GS21 - 230 mg/kg/day glucosamine sulphate for 21 days; OVx 45 - treated with NaCl 0.9% as above for 45 days; and OVx - GS45230 mg/kg/day glucosamine sulphate for 45 days. Seven intact animals in the proestrous phase were used as controls (CG). Upon treatment completion, the animals were sacrificed and the left knee joint was dissected and prepared for histological analysis. RESULTS: The percentage of remaining cartilage in new bone of the CG; that found in THE OVx GS45 group was significantly less than that of the OVx 21, OVx GS21, and OVx 45 groups. The percentage of trabecular bone in proestrous animals was the highest. The OVx GS45 group showed higher values compared with the other ovariectomized groups. These results were paralleled by the findings regarding the cells of the proliferative zone, since the CG had the highest values, and the values of the OVx GS45 group were greater than those of the OVx 21, OVx GS21, and OVx 45 groups. CONCLUSION: Our studies suggested that glucosamine may stimulate tibial cartilage and bone growth after ovariectomy in rats.